Effects of wet and dry milling conditions on properties of mechanically alloyed and sintered W–C and W–B4C–C composites - Uenal, N.; Oevecoglu, M. L. (SAGE Publications, 2009)
AbstractTungsten based W–1C and W–2B4C–1C (wt-%) powders synthesised by mechanical alloying (MA) for milling durations of 10, 20 and 30 h, in wet (ethanol) and dry conditions, were characterised. X-ray fluorescence spectroscopy investigations revealed Co contamination which increased with increasing milling time during wet milling. X-ray diffraction investigations revealed the presence of W and WC phases in all powders, Co3C intermetallic in the wet milled W–1C powders and W2B intermetallic phase in both wet and dry milled W–2B4C–1C powders. As blended and MA processed powders were consolidated into green compacts by uniaxial cold pressing at 500 MPa and solid phase sintered at 1680°C under hydrogen and argon atmospheres for 1 h. X-ray diffraction investigations revealed the presence of W2C intermetallic phase in sintered composites produced from both wet and dry milled W–1C powders and the W2B intermetallic phase in sintered material from the wet milled W–2B4C–1C powder. Sintered composites from wet mill...